Evaluating the Safety Profile of Propofol Sedation in Patients Undergoing Endoscopic Variceal Band Ligation: A Comprehensive Analysis - Arslan Shahzad; Minahil Ramzan; Muhammad Tahir; Muhammad Zuhair Tahir; Muhammad Zubair Tahir; Muhammad Babar Shahzad (Journal of Rawalpindi Medical College)
Objective: To find out the incidence of complications of Endoscopic Variceal Band Ligation, when done under Propofol sedation.